CURRENT STATE OF DEVELOPMENT OF FINANCIAL SUPPORT FOR PRESCHOOL EDUCATION BASED ON PPP BASED ON THE EXAMPLE OF THE REPUBLIC OF KARAKALPAKSTAN - Turdiyeva Yakitjan Khayitbayevna (Scholars Digest Publishing, 2025)
Preschool education represents an important element of the education system, providing the foundation for the further development of the child. In the context of modern economic realities, state budgets often experience deficits, which makes it difficult to finance social programs, including the sphere of preschool education. In such conditions, special attention is paid to alternative ways of attracting funds, one of which is the use of the public-private partnership (PPP) mechanism. The Republic of Karakalpakstan, as part of Uzbekistan, is actively researching and implementing these approaches to improve the quality of preschool education.
Keywords: PPP, social security, investments, subsidies, institutional base, infrastructure.